Comparação da gravidade das crises de sibilância em lactentes causadas por diferentes vírus respiratórios - Silva, Jacqueline Ramos da (2013)
Acute wheezing is a leading cause of hospitalization in infants. Previous studies have described a difference in the severity of the disease depends on the virus identified in a sample of air, but some studies show conflicting results. This study is therefore to evaluate the relationship between the causative pathogen of lower respiratory tract infection (LRTI) and length of stay in a sample of infants from Porto Alegre. The nasopharyngeal specimens for testing of respiratory viruses by immunofluorescence and polymerase chain reaction were collected between 09/2009 and 09/2011. We recruited patients at the Hospital São Lucas diagnosed with LRTI. We analyzed 122 samples from patients with LTRI, and of these, 65 (51.2%) were positive for respiratory syncytial virus infection (RSV). Besides these samples, 15 were positive for influenza, 5 to rhinovirus, parainfluenza to 10, 3 to metapneumovírus and 3 for adenovirus. When we used length of stay as a marker of severity, patients with RSV were, on average, 6.74 ± 4.39 days hospitalized, while patients infected with other viruses were only 4.97 ± 2.64 days hospitalized, on average; this difference was statistically significant. However, when we used other risk factor as family history of asthma, number of siblings and sex, there was no significant difference. The study demonstrated high overall positive tests for virus, with the predominance of RSV. The study suggests that RSV may be considered as a risk factor for ITRI severity